2022
DOI: 10.1186/s12884-022-05020-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal dietary carbohydrate intake and vitamin D-related genetic risk score on birth length: the Vitamin D Pregnant Mother (VDPM) cohort study

Abstract: Background Our objectives were to investigate the relationship between maternal vitamin D status and IGF-1 levels in healthy Minangkabau pregnant mothers and their impact on newborn anthropometry outcomes and to examine whether this relationship was modified by dietary intake using a nutrigenetic approach. Methods Healthy singleton pregnant mother and infant pairs (n = 183) were recruited. We created three genetic risk scores (GRSs): a six-SNP GRS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…In our study, carbohydrate intake was significantly negatively correlated with 25(OH)D levels in the group with high carbohydrate intake, i.e., ≥300 g/day carbohydrate intake which was based on two-fold between EAR and RDA from IOM (U.S.) and Taiwan’s Dietary Reference. Only a few studies have addressed the relationship between VD and high carbohydrate intake [ 17 , 18 ]. Bolesławska et al reported that the 25(OH)D concentration was significantly higher in the low-carbohydrate-high-fat diet group than in the Eastern European diet group [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, carbohydrate intake was significantly negatively correlated with 25(OH)D levels in the group with high carbohydrate intake, i.e., ≥300 g/day carbohydrate intake which was based on two-fold between EAR and RDA from IOM (U.S.) and Taiwan’s Dietary Reference. Only a few studies have addressed the relationship between VD and high carbohydrate intake [ 17 , 18 ]. Bolesławska et al reported that the 25(OH)D concentration was significantly higher in the low-carbohydrate-high-fat diet group than in the Eastern European diet group [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have addressed the relationship between Vitamin D and carbohydrate intake. Nutrigenetic studies in Indonesia demonstrated that the relationships between vitamin D, body fat percentage and newborn anthropometry was modified by high carbohydrate intake (mean 405 g/day and 319 g/day carbohydrate intake) [ 17 , 18 ]. But there was no exact cut-off value of high carbohydrate intake in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…The instrument for measuring the height of the body (cm) uses the type Microtoise Staturemeter with units (cm), the smallest unit 0 cm and the largest unit 200 cm. The body height measuring brand is GEA MEDICAL manufactured by Changzou Wujin Weiging Apparatus Factory, China (16)(17)(18).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, this interaction was shown to have a discernible impact on outcomes related to birth length. In fact, pregnant women with elevated carbohydrate intake and two or more risk alleles of VDR-GRS had newborns with considerably shorter birth lengths in comparison to infants born to mothers with fewer than two risk alleles [38].…”
Section: Anthropometric Measuresmentioning
confidence: 98%